Edukasi Penanggulangan Hipertensi dan Pemanfaatan Bahan Alam Berbasis Kearifan Lokal pada Petani Jambu Biji Merah di Jatirejo, Ngargoyoso: Education on Hypertension Management and the Utilization of Local Wisdom-Based Natural Resources for Red Guava Farmers in Jatirejo, Ngargoyoso - Aulia Nur Rahmawati; Alip Desi Suyono Saputri; Truly Dian Anggraini; Bayu Kurniaaji; Pranichayudha Rohsulina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Farmers in Jatirejo Village, Ngargoyoso, under the P4S Putra Jambu association, play a dual role as guava cultivators and agritourism educators. High physical demands and unhealthy lifestyles, such as smoking and high sugar/salt intake, increase the risk of hypertension and occupational stress, potentially hindering their productivity. This community service aims to enhance farmers' knowledge and awareness of hypertension prevention through health education and the utilization of local natural resources. Methods: The program was conducted in October 2025 and involved 27 farmers. Methods included education using the